A organização do trabalho pedagógico da Educação Física e a pedagogia histórico-crítica: limites e possibilidades - Alves, Naiá Márjore Marrone (2018)
This work has as object of study the organization of the pedagogical work of Physical Education in the light of historical-critical pedagogy. The central question that guided the whole realization of this research was: "What are the limits and possibilities for the implementation of a pedagogical proposal of Physical Education from the historical-critical pedagogy in the organization of the pedagogical work of a state school in Itaberaí"? The general objective of the research was to investigate and analyze the limits and possibilities for the implementation of a pedagogical proposal of Physical Education from the historical-critical pedagogy in the organization of the pedagogical work in a state school of Itaberaí-GO. As specific objectives, we highlight: a) to investigate the role and the insertion of Physical Education in the organization of the pedagogical work of the Honestino Monteiro Guimarães Center for Integral Teaching; b) identify and analyze the conceptions of Physical Education used in the discourses of the school community (teachers, students and management team); c) systematize a proposal of Physical Education from the historical-critical pedagogy and apply it to the students of the 3rd year of high school of this school; d) to identify and analyze, from the proposed systematization, the limits and possibilities for working with the contents of Physical Education from the Pedagogy of History in this school. We work with the hypothesis that it is possible to implement a pedagogical proposal for Physical Education from the historical-critical pedagogy in the organization of the pedagogical work of the school, even in spite of the inherent limits to the contradictions found in an institution that is a driving force dominant mode of production. The group chosen for the implementation of the proposal was the 3rd year of high school. The content was football. Semi-structured questionnaires, semi-structured interviews, documentary analysis, free observation and field diary were used as research instruments. As a data collection technique, we use content analysis. The theoretical framework of this research is historical-critical pedagogy, critical-overcoming pedagogy and historical-cultural psychology, whose references are found in Dermeval Saviani, Newton Duarte, Lígia Márcia Martins, Micheli Ortega Escobar, among others. It is a study and case of a critical-dialectical and qualitative approach. The product of this research will be a didactic sequence elaborated from the intervention proposal that was developed. Our provisional synthesis allows us to affirm that the organization of the pedagogical work of Physical Education in the researched school has reflected the designs of the capitalist school. However, through the intervention carried out, it was found that it is possible to promote ruptures from a pedagogical work guided by historical-critical pedagogy.